Содержательные и функционально-коммуникативные свойства речевого акта одобрения (на материале англоязычного художественного дискурса) - Бігунова, Наталія Олександрівна; Bigunova, N. O. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті аналізуються функціонально-комунікативні ознаки мовленнєвого акту схвалення в англомовному художньому діалогічному дискурсі. Вивчено іллокутивні цілі та перлокутивний ефект мовленнєвого акту схвалення, визначений об’єкт мовленнєвого акту схвалення; класифіковано лексичні та граматичні засоби висловлення схвалення. The article analyses functional-communicative characteristics of approval speech act in English artistic dialogic discourse. It also reports on the illocutionary aims and the perlocutionary effect of approval speech act in English artistic dialogic discourse. The article includes the definition of the approval speech act object and the classification of the lexical and grammatical devices expressing approval.
Content and functional-communicative Characteristics of Approval Speech act (on the Samples from English Artistic Discourse)
Keywords: оцінка; evaluation; мовленнєвий акт; speech act; схвалення; approval